MORPHOLOGY OF PALATINE TONSILS IN CHRONIC TONSILLITIS IN IDENTICAL TWINS - Arifov S. S; Nurov U. I. (International Engineering Journal For Research & Development, 2020)
The work is devoted to one of the actual problems of otorhinolaryngology in the study of morphological changes in the tonsils in the chronic course of inflammation in monozygous twins and to compare them with morphological changes in inflammation of the tonsils in non-twins. This work is based on studies of a micropreparation of palatine tonsils after tonsillectomy in 12 pairs of identical twins operated in the ENT department of the Bukhara multiprofile children's hospital from 2000 to 2018.The anatomical location of the palatine tonsils and histological studies are described in detail. The results show that after tonsillectomy for chronic tonsillitis in twins and non-twins, as well as between two twins in structure, in the morphometric parameters of the tonsils and in the vascular system, there are no significant differences. In both twins, the picture of the inflammatory process looks the same. and is no different from the tonsils in non-twins.